Phenomenological study Elwction of Labor Medicine on Primigravid Mother Reviewed From Anxious Management Equipment: Labor Medicine - Saharudin Nisi (Politeknik Karya Persada Muna, 2021)
Baground: coverage of delivery assistance by health personnel in order to achieve healthy Indonesia is 90%. This excessive anxiety will affect the readiness of the mother in preparing for the delivery of the mother's maternal care determination. the purpose to be achieved from this research is to analyze the reason of decision of mother to choose shaman as birth helper in terms of management of labor anxiety in working area of Parigi Sub-district of Muna Regency. Method: The type of research used is qualitative research using indepth interview. While theory behavior used is the theory of reasoned action. Number of informants as many as 10 people. This interview method was conducted during the visit to each respondent's Results: After seeing informant information about shaman election as labor aid helper then it can be analyzed that there is in working area of Parigi Puskesmas pregnant mother prefer shaman baby with reason of experience owned, their attitude toward society better, care given very good, attitude weak gentle and mythical thriving in society Conclusions: It can thus be concluded that the behavior of mothers in the selection of shamans as birth attendants is influenced by anxious feelings about the safety of mothers and infants with the assumption that the shaman is more comfortable compared to the health worker who is inculcated in experience, family support and social or social norms values myths are growing in the community Keywords: Birth Helper, Shaman, Mother Anxiety